Mapping disciplinary differences and equity of academic control to create a space for collaboration - Siemens, Lynne; Smith, Jeff; Liu, Yin (Canadian Journal of Higher Education, 2014)
Academics are collaborating more as their research questions are becoming more complex, often reaching beyond the capacity of any one person. However, in many parts of the campus, teamwork is not a traditional work pattern, and team members may not understand the best ways to work together to the benefit of the project. Challenges are particularly possible when there are differences among the disciplines represented on a team and when there are variations in academic control over decision making and research direction setting. Disparities in these two dimensions create potential for miscommunication, conflict, and other negative consequences, which may mean that a collaboration is not successful. This paper explores these dimensions and suggests a space for collaboration; it also describes some benefits and challenges associated within various positions within the framework. Academic teams can use this tool to determine the place they would like to occupy within the collaboration space and structure themselves accordingly before undertaking research.